2018
DOI: 10.17576/mjas-2018-2201-18
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alkali Treatment on Physico-Chemical Properties of Malaysian Bamboo Fiber: A Preliminary Study

Abstract: In the present study, the effect of alkaline treatment on the morphology and physico-chemical properties of Malaysian bamboo fibers was elucidated. The fibers were extracted from raw bamboo culm using alkaline solution with concentrations of 0 and 10 wt% at 24 hours and followed by roller milling techniques. The treated and untreated fibers were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and scanning electron microscope (SEM). Apart from that, the mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Several studies reported that alkaline treatment decrease lignin content, especially at high concentration (Maulana et al 2021a;Yang et al 2019). Another study found a similar outcome reported by Tong et al (2018) that alkaline immersion treatment with 10% NaOH for 24 h partially removed the lignin content. This study shows that klason lignin content decreased event at a low concentration of alkali and shorter immersion time.…”
Section: Klason Lignin Contentsupporting
confidence: 82%
See 1 more Smart Citation
“…Several studies reported that alkaline treatment decrease lignin content, especially at high concentration (Maulana et al 2021a;Yang et al 2019). Another study found a similar outcome reported by Tong et al (2018) that alkaline immersion treatment with 10% NaOH for 24 h partially removed the lignin content. This study shows that klason lignin content decreased event at a low concentration of alkali and shorter immersion time.…”
Section: Klason Lignin Contentsupporting
confidence: 82%
“…The decrease in lignin content was such an advantage for biocomposite material. Partially lignin removal may alter fiber's tensile and surface roughness properties (Hashim et al 2017;Setiawan et al 2019;Tong et al 2018). Thus, the fibers were easier to bond with the adhesive.…”
Section: Klason Lignin Contentmentioning
confidence: 99%
“…The peak at 1513 cm -1 was derived from the C=C stretching of lignin [35]. It has been reported that the alkaline treatment using 10 wt% NaOH of bamboo fibers resulted in the partial removal of lignin and hemicellulose [36]. The peaks around 1025 cm -1 [37] and 790 cm -1 [38] related to the O-Si-O bonds in SiO2 of untreated RH and treated RH1.…”
Section: Structurementioning
confidence: 99%
“…Surface treated RH was rough and improved the adhesion with HDPE matrix. Tong et al studied the effect of high alkaline concentration (10 wt% NaOH) on bamboo fiber, the morphology and physico-chemical properties on treated fibers [36]. The treated and untreated fibers were characterized by FTIR, thermogravimetric analysis (TGA), and SEM.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fiber has advantages as a sustainable, environmentally friendly and low-cost construction material. In the past, most of the investigations on natural fiber composites such as kenaf [29], bamboo [18,24,35], jute [16], sisal Ramesh et al [26] focused on their physical, mechanical and thermal properties, effects of fiber extraction methods as well as types of fiber treatment. Due to the high tensile strength and tensile modulus of natural fibers, further investigations were conducted to study the potential of natural fiber reinforced composites for structural strengthening.…”
Section: Introductionmentioning
confidence: 99%